Perbandingan Hasil Belajar Biologi Menggunakan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Dengan Tipe Teams Assisted Individualization (TAI) Kelas VIII SMP Negeri 2 Batang Kapas - Afra Diwanto, Bhusry; Megahati S, Megahati S; Fitriani, Vivi (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The result of biology learning process of VIII grade in SMP 2 Batang Kapas is low, because the learning process that has been done for all this time only listening, watching, and doing tasks given by teacher. Students are not be able to connect the facts were found when solving problem. Students only memorize the facts, but they can not understand that facts by their own mind. This leads them to a monotonous situation and students become inactive in the learning process. The consequences are students feel boring fast, donât get serious in learning process, and finally, the lessons are felt difficult to learn by students. The purpose of this observation was to compare the outcomes of biology learning process of students using the types of cooperative learning model, that are Numbered Head Together (NHT) and Teams Assisted Individualization (TAI) of VIII Grade in SMP N 2 Batang Kapas. This study has been done in September-October2013 in eighth grade in Â SMP N 2 Batang Kapas in first term. This research is an experimental research design with Randomized Control Group posttest Only Design. The population of this research is the eighth grade students of SMP N 2 Batang Kapas listed on the Academic Year2013/2014. Technic data analysis used was t test. Based on the result of the analysis of the data found that both classes of normally distributed and homogeneous samples. Hypothesis test results obtained thitung value of 1.03 while ttable 1.67, meaning thitung <ttable, then the hypothesis in this study is H0Â is accepted. It can be concluded that there is no difference in learning outcomes biology students using cooperative learning model Numbered Head Together (NHT) with type Teams Assisted Individualization (TAI) VIII grade in first term in SMP N 2 Batang Kapas.Â